Designing dithienonaphthalene based acceptor materials with promising photovoltaic parameters for organic solar cells. Issue 59 (28th October 2019) - Ans, Muhammad; Iqbal, Javed; Bhatti, Ijaz Ahmad; Ayub, Khurshid
Abstract : We have designed dithienonaphthalene based A–D–A materials for higher PCE. Our designed molecules have same donor unit with different end-capped acceptor units. All designed molecules are investigated with DFT and TD-DFT approaches. Abstract : Scientists are focusing on non-fullerene based acceptors due to their efficient photovoltaic properties. Here, we have designed four novel dithienonaphthalene based acceptors with better photovoltaic properties through structural modification of a well-known experimentally synthesized reference compound R . The newly designed molecules have a dithienonaphthalene core attached with different acceptors (end-capped). The acceptor moieties are 2-(5, 6-difluoro-2-methylene-3-oxo-2, 3-dihydroinden-1-ylidene)malononitrile (H1 ), 2-(5, 6-dicyano-2-methylene-3-oxo-2, 3-dihydroinden-1-ylidene)-malononitrile (H2 ), 2-(5-methylene-6-oxo-5, 6-dihydrocylopenta[ c ]thiophe-4-ylidene)-malononitrile (H3 ) and 2-(3-(dicyanomethylene)-2, 3-dihydroinden-1-yliden)malononitrile (H4 ). The photovoltaic parameters of the designed molecules are discussed in comparison with those of the reference R . All newly designed molecules show a reduced HOMO–LUMO energy gap (2.17 eV to 2.28 eV), compared to the reference R (2.31 eV). Charger transfer from donor to acceptor is confirmed by a frontier molecular orbital (FMO) diagram. All studied molecules show extensive absorption in the visible region and absorption maxima are red-shifted compared to R . All investigated molecules have lower excitation energies which reveal high charge transfer rates, as compared to R . To evaluate the open circuit voltage, the designed acceptor molecules are blended with a well-known donor PBDB-T . The molecule H3 has the highest V oc value (1.88 V). TDM has been performed to show the behaviour of electronic excitation processes and electron hole location between the donor and acceptor unit. The binding energies of all molecules are lower than that of R . The lowest is calculated for H3 (0.24 eV) which reflects the highest charge transfer. The reorganization energy value for both the electrons and holes of H2 is lower than R which is indicative of the highest charge transfer rate.